A tempest of tea - Faizal, Hafsah (Blood and tea, 2024)
"On the streets of White Roaring, Arthie Casimir is a criminal mastermind and collector of secrets. Her prestigious tearoom transforms into an illegal bloodhouse by dark, catering to the vampires feared by society. But when her establishment is threatened, Arthie is forced to strike an unlikely deal with an alluring adversary to save it--and she can't do the job alone. Calling on some of the city's most skilled outcasts, Arthie hatches a plan to infiltrate the dark and glittering vampire society known as the Athereum. But not everyone in her ragtag crew is on her side, and as the truth behind the heist unfolds, Arthie finds herself in the midst of a conspiracy that will threaten the world as she knows it." --